Human microbiome, applied to clinical practice - V. T. Ivashkin; K. V. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. The Human microbiome project was designed for identification and characterization of set of human microorganisms as well as for studying the changes in the human health due to microbiome changes. The Human Genome Project assumes: development of the human genome variations database (HapMap; Human Variome Project), interpretation of human phenotype differences (Encyclopedia Of DNA Elements), modeling of human phenomenon (RECON), interpretation of epigenetic variants and hereditary changes in phenotypical manifestations. The Human Microbiome Project became the sequel of The Human Genome Project. Summary. The human microbiome represents a variety of microbial species with the differing metabolic activity. The main features of human microbiome include: great variety at the level of genus and at the level of species, varying modes of diversification within samples, variability of microbiome of separate individuals is much less in comparison to interindividual variability, metabolic pathways remain unchanged until the patient is healthy, the lack of pathogenic bacteria in healthy microbiomes serves as microbiota alteration evidence in the state of disease. Identification of «microbial core» in microbial taxon remains a fundamental problem. There is a need to study of possible effects of altered microbiome on drug interactions and the immune status. The model of bacterial involvement in colorectal cancer progression is under study. Besides, the increasing attention of doctors and scientists is attracted to the issue intestinal microflora changes at antibiotic treatment. Conclusion. «The Human microbiome project» is implemented within identification and characterization of the microorganisms associated to the different anatomical regions of the human body tasks of the project include the study of inand interindividual microbiome disorders and their possible effect on the human health. The theory and practice of microbiome causes high potential for justification of the pattern of healthy nutritional pattern, behavior and development of new therapeutic agents.